Alkaline phosphatase activity is unregulated in regenerating human periodontal cells - KURU, LEYLA (WILEY, 1999)
The activity of alkaline phosphatase (ALP) is considered to indicate the presence of osteoblast cells and the formation of new bone. In the present study this enzyme was investigated in cells obtained from retrieved polytetrafluoroethylene membranes (M cells) of periodontal disease patients treated by guided tissue regeneration (GTR) and from the regenerated tissue underlying the membrane (RT cells). Normal periodontal ligament (PL) and gingival cells were also grown from the corresponding healthy tissues of human subjects. ALP activity was measured colourimetrically, using paranitrophenyl phosphate as the substrate, after 4 and 7 d of culture in the absence and presence of dexamethasone (DEX), a synthetic glucocorticoid which induces osteoblast differentiation. The results showed that basal levels of ALP activity were expressed by all the cells and that DEX upregulated ALP levels in the M, RT and PL cells but not in the gingival cells. Moreover, both the basal and DEX-induced ALP activities were statistically significantly higher in the RT cells than in any of the other cells. Our results suggest that both the GTR-associated and normal PL cells express osteoblast-like characteristics and, furthermore, that the RT cultures in particular contain a high proportion of osteoprogenitor cells.
Keywords: alkaline phosphatase activity; GTR; cell culture; dexamethasone; GUIDED TISSUE REGENERATION; EXPANDED POLYTETRAFLUOROETHYLENE MEMBRANES; HUMAN INFRABONY DEFECTS; IMMUNOHISTOCHEMICAL ANALYSIS; ATTACHMENT FORMATION; LIGAMENT; DIFFERENTIATION; FIBROBLASTS; ADHERENT; MARROW